Apology Strategies of Algerian University Students of English - Allili, Souad (Journal of Human Sciences, 2016)
The current study aims at investigating the apology strategies employed by Algerian university students of English relative to the factors of social power, distance and severity of the offense. The data for analysis in this study were collected through a Discourse Completion Questionnaire and interviews. The findings revealed that the respondents preferred giving direct expressions of apology and taking on responsibility more than the other strategies. The informants also resorted to new strategies namely, a call to hold anger, determinism and arrogance. The results further showed that the severity of the offense was the predominant factor that determined the selection and intensity of apology strategies. All the interviewees agreed that apology speech act maintains harmony among people.